Effect of sulfide films formed on X65 steel surface on hydrogen permeation in H2S environments. (16th February 2017) - Huang, F.; Cheng, P.; Zhao, X.Y.; Liu, J.; Hu, Q.; Cheng, Y. Frank
Abstract: In this work, the morphology, structure and ion-selectivity of surface sulfide films formed on an X65 pipeline steel in solutions with various pH values and H2 S concentrations were characterized, and the effect of the film on hydrogen permeation was investigated. Results demonstrated that crystalline iron sulfide (FeS) and/or mackinawite forms on the steel surface during H2 S corrosion, depending on the H2 S concentration and the solution pH. The presence of sulfide films blocks the hydrogen permeation through the steel, and the blocking effect increases with the increasing H2 S concentration and reducing pH value. Compared to the film containing crystalline FeS only, the mixed compositions of mackinawite and FeS in the film cause an increased effect to block hydrogen permeation. The sulfide films are an n -type semiconductor with the anion selectivity, which, combined with the film thickness, contributes to the blocking effect on hydrogen permeation into the filmed steel. Highlights: Crystalline FeS and/or mackinawite forms on steel during H2 S corrosion. The H2 S concentration and solution pH affect the product films. The sulfide films block hydrogen permeation through the steel. There is an increased blocking effect of mixed mackinawite and FeS films.